From Greek paideia to modern educational systems: evidence for the need to integrate physical activity into academic settings - Fraile-Martinez, Oscar; García-Montero, Cielo; Fraile-Martinez, Marcos; Pekarek, Leonel; Barrena-Blázquez, Silvestra; López-González, Laura; Álvarez-Mon, Miguel Angel; Pekarek, Tatiana; Casanova, Carlos; Álvarez-Mon, Melchor; Saez, Miguel A.; Diaz, Raul; et al. (Frontiers in Education, 2025)
The ancient Greek educational system, based on paideia, sought to shape well-rounded citizens through the integration of physical and intellectual education, thus promoting a balance between body and mind. This educational philosophy, centered on holistic development, was embodied in institutions such as the gymnasium, where physical training not only strengthened the body but also enhanced the character and morality of young people. In the current context, scientific studies have shown that physical activity within the academic environment significantly improves both physical and mental health, enhances cognitive performance, and counteracts increasingly prevalent issues in our society, such as sedentary behavior, obesity, depression, and anxiety among students. Despite this evidence, current educational systems tend to prioritize intellectual learning over physical education, posing a challenge for modern education. Given that most students lack sufficient time for exercise, there is a growing need to reform school curricula to more effectively integrate movement and exercise. This review examines the educational value of paideia and the Greek gymnasium as fundamental historical antecedents for contemporary educational systems, exploring studies that support the need to place greater emphasis on physical activity and various models that can be implemented in the actual academic context. Likewise, different barriers, challenges and opportunities for a better integration of physical activity in modern educational systems will be summarized as well. Drawing inspiration from the Greek model of body–mind integration can offer a more balanced and health-oriented approach to student development, promoting not only their physical and mental well-being but also their readiness to face contemporary challenges.